2008
DOI: 10.1002/jso.21205
|View full text |Cite
|
Sign up to set email alerts
|

Rapid autonomisation of a combined fibular‐ and anterolateral thigh flap transferred by a wrist carrier to an irradiated and vessel depleted neck

Abstract: In an irradiated and vessel depleted neck, we used the wrist carrier technique to provide flap perfusion until autonomisation took place. A combined anterolateral thigh- and osteocutaneous fibular flap was anastomosed to the radial vessels of an irradiated patient with a vessel depleted neck for reconstruction of the lower face. Periodical pedicle occlusion started immediately after surgery. On day 16, cutaneous blood flow and oxygenation were still reduced, but wound healing was uneventful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
2
14
0
1
Order By: Relevance
“…On the other hand, clinical reports describe complete flap survival despite early disruption of the pedicle (Chen et al, 2002;Salgado et al, 2002;Wolff et al, 2003Wolff et al, , 2009Wise et al, 2011); this has also been shown in experimental work (Civelek et al, 2009;Mucke et al, 2011). In all three patients, 10e13 days of extracorporeal perfusion were sufficient for bone and muscle tissue, but not for the large skin paddle in patient 1.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…On the other hand, clinical reports describe complete flap survival despite early disruption of the pedicle (Chen et al, 2002;Salgado et al, 2002;Wolff et al, 2003Wolff et al, , 2009Wise et al, 2011); this has also been shown in experimental work (Civelek et al, 2009;Mucke et al, 2011). In all three patients, 10e13 days of extracorporeal perfusion were sufficient for bone and muscle tissue, but not for the large skin paddle in patient 1.…”
Section: Discussionsupporting
confidence: 54%
“…Repetitive occlusion of the vascular bridge was performed to induce gradually increasing ischemic periods. By doing so, flap autonomisation occurred as early as day 16 and 18, respectively (Wolff et al, 2003(Wolff et al, , 2009. Other clinical reports have described a complete survival of free flaps after an inadvertent early disruption of the blood supply between days 7 and 17 (Chen et al, 2002;Wise et al, 2011), but not in irradiated defects (Salgado et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although these findings support the importance of an intact vascular pedicle for permanent flap survival, especially in irradiated recipient sites, other reports document early autonomization which became evident after division of the pedicle during the first days after surgery 11, 12, 17–20. According to these well‐documented clinical cases, neovascularization seems to be capable of sustaining the flap from about 5 days post surgery.…”
Section: Discussionmentioning
confidence: 68%
“…Autonomization of free flaps was defined as stable HbO 2 and CF during the performed O2C measurements. According to the literature, values of HbO 2 above 20 AU and CF above 20 AU after at least 1 min of pedicle compression was defined as autonomized 9–11. Measurements below these values were defined as not autonomized flaps, and all of these flaps showed values of HbO 2 developing to 0–5 AU after about 2 min.…”
Section: Resultsmentioning
confidence: 99%